Dorsal Augmentation Using Autologous Costal Cartilage or Microfat-Infused Soft Tissue Augmentation - Toriumi, Dean M. (Facial Plastic Surgery, 2017)
Costal cartilage grafting is increasing in popularity with increased demand for augmentation rhinoplasty and increased need for grafting material for structure rhinoplasty techniques. Use of costal cartilage for dorsal grafting is both art and science. The art is demonstrated in the act of carving a dorsal graft that will reflect the actual contour of the nasal dorsum. The science is linked to the methodology of how the grafts are contoured to match the patient's desires and how the graft is fixed to the bony dorsum to minimize the risk of warping and displacement. Variations in dorsal graft design and methods of fixation are described. Use of the perichondrial interface between dorsal graft and perforated/rasped nasal dorsum acts to ossify the dorsal graft to the underlying bone, creating an immobile and natural appearing nasal dorsum. The fixation of the dorsal graft limits movement and hence decreases the likelihood of warping or deformity. Use of microfat in rhinoplasty has tremendous potential for camouflage and to promote healing of compromised tissues. Using microfat-infused soft tissue augmentation (MISTA), the surgeon is able to deliver microfat to an open surgical field, promote healing, and provide soft tissue augmentation. In this technique, microfat is injected into soft tissue carriers (perichondrium, temporalis fascia, etc.) and then implanted into the surgical field. MISTA has tremendous potential utility in many areas of cosmetic and reconstructive surgery.
Keywords: costal cartilage; dorsal augmentation; Asian rhinoplasty; rib cartilage; microfat in rhinoplasty; microfat-infused soft tissue augmentation